Swarm stability and optimization - Gazi, Veysel (Springer, 2011)
Swarming species such as flocks of birds or schools of fish exhibit fascinating collective behaviors during migration and predator avoidance.  Similarly, engineered multi-agent dynamic systems such as groups of autonomous ground, underwater, or air vehicles (vehicle swarms) exhibit sophisticated collective behaviors while maneuvering. In this book we show how to model and control a wide range of such multi-agent dynamic systems and analyze their collective behavior using both stability theoretic and simulation-based approaches. In particular, we investigate problems such as group aggregation, social foraging, formation control, swarm tracking, distributed agreement, and engineering optimization inspired by swarm behavior.